The Effects of HCG on the Distribution Pattern of Mature Pregnant Rat Uterine Glycoconjugates during Implantation Period - Elham Aliabadi; Zohreh Makoolati; Tahereh Talaei-Khozani; Fakhreddin Mesbah Ardekani (Negah Institute for Scientific Communication, 2013)
Introduction: One of the most common reasons of infertility is un-ovulatory period. Hormone therapy is the most common treatments of this type of infertility. Gonadotropins may exert toxic effects on the molecular organization of uterine surface, such as glycoconjugates. Glycoconjugates are the most important components of the uterine and trophoblast surface playing an important role in embryo implantation. In this study, the effects of one of these gonadotropin hormones, Human Chorionic Gonadotropin (HCG), on glycoconjugates distribution of uterine epithelium (apical membrane, Golgi zone and basement membrane of rat endometrial cells) and uterine glands studied during implantation period. Methods: The mature female rats were selected and divided into two groups (Experimental, sham and Control). Experimental rats were injected with 10 I.U HCG intraperitoneally in estrus phase and mated with proven fertile male rats. The rats were sacrificed at 5.5 day of pregnancy (time of implantation) and their uteruses removed. The pregnant uterine tissues prepared histologically. Using WGA, DBA, PNA, ConA, SBA and UEA lectins, Lectin histochemistry was done. Results: The intensity of the reactions to WGA in apical membrane and Golgi zone of the uterine epithelium were lower in HCG-treated group compared with the control group. After HCG treatment, uptake of DBA and UEA lectins by uterine glands was low. Conclusion: HCG led to modification of the uterine surface glycoconjugates and affected the content of these critical molecules involved in implantation. Therefore, HCG may also exert adverse impact on the fertility rate.